Development of Teaching Materials in Curriculum Studies and History Textbooks - Rivasintha Marjito, Emusti; Hidayat, Sahid (HISTORIA: Jurnal Program Studi Pendidikan Sejarah, 2024)
The aim of this research is to determine the development of scientific-based teaching materials in curriculum study courses and history textbooks. This research uses the R & D method, with the research model being the ADDIE model. From the research results, it was found that the percentage attainment level for the appropriateness of teaching materials was 87.5% after being adjusted to the feasibility table, the percentage achievement level of 87.5% was in very good qualifications. The development of teaching materials is very helpful and influences many things, starting from students being more active in learning, making it easier for students to understand the material being taught, and students enjoying lessons without feeling bored. Then the influence of the development of teaching materials for teachers or lecturers, teachers become more creative in developing teaching materials. Because developing teaching materials is not just floating around, teachers or lecturers are also required to follow the development of their students and be active and creative in looking for something that can be used in teaching. Teaching materials are also said to be of quality if they are interesting and of course relevant to learning and are appropriate, timely, and targeted. We can create teaching materials by looking for used materials which we modify as teaching materials, we can also search in libraries and other sources.